Is it because of boredom or workload? a multilevel investigation of the effects of workload and job boredom on daily work outcomes - Avcı, Ayla; Çetin, Metin (İdeal Kent Yayınları, 2023)
Studies report that both job boredom and excessive workload have detrimental effects on employee well-being and work outcomes. Although these variables fluctuate daily, longitudinal studies addressing within- and between-person variance in the variables and how they relate to daily work outcomes are scarce. The aim of this study was to determine how daily workload and daily job boredom are associated with daily emotional labor, stress, job satisfaction, and positive and negative affect. Multilevel data were collected at six time points (five daily, one person level). Person level (n=137) and day level (685) data were matched to conduct multilevel analyses using the software HLM. Both workload and job boredom showed substantial daily variability. The results of multilevel analyses revealed that job boredom had wider negative effects than workload in general. While daily job boredom was positively related to work stress, negative affect, and emotional labor, it demonstrated a significant negative relationship with positive affect. Daily workload was significantly related to only stress and negative affect. Using multilevel methods, it is possible to investigate the variance and relationships of the concepts both at general and daily levels. The results emphasize the negative effects of daily job boredom, which can be more critical compared to workload. The results also have important practical implications for managers.

Literatür hem iş sıkıntısının hem de aşırı iş yükünün çalışanların refahı ve iş sonuçları üzerinde zararlı etkileri olduğunu bildirmektedir. Bu değişkenler günlük olarak dalgalansada, değişkenlerdeki kişi içi ve kişiler arası varyansı ve bunların günlük iş sonuçlarıyla nasıl ilişkili olduğunu ele alan boylamsal çalışmalar azdır. Bu çalışmanın amacı, günlük iş yükü ve günlük iş sıkıntısının günlük duygusal emek, stres, iş tatmini ve olumlu ve olumsuz duygulanım ile nasıl ilişkili olduğunu belirlemektir. Çalışma kapsamında altı farklı zaman noktasında çok düzeyli veri toplanmıştır (beşi günlük ve biri kişi düzeyinde). HLM yazılımı kullanılarak çok düzeyli analizler yapmak için kişi düzeyi (n=137) ve gün düzeyi (685) veriler eşleştirilmiştir. Hem iş yükü hem de işten sıkılma değişkenlerinin önemli ölçüde günlük varyans gösterdiği saptanmıştır. Çok düzeyli analizlerin sonuçları, işten sıkılmanın genel olarak iş yükünden daha geniş olumsuz etkilere sahip olduğunu ortaya koymuştur. Günlük iş sıkıntısı, iş stresi, olumsuz duygulanım ve duygusal emek ile olumlu yönde ilişkiliyken, olumlu duygulanım ile anlamlı bir ilişki göstermiştir. Günlük iş yükünün, yalnızca stres ve olumsuz duygulanımla anlamlı seviyede ilişkili olduğu bulgulanmıştır. Çok düzeyli yöntemler kullanılarak hem genel hem de günlük düzeyde kavramların varyans ve ilişkilerinin araştırılması mümkündür. Sonuçlar, iş yüküne kıyasla daha kritik olabilen günlük iş sıkıntısının olumsuz etkilerini vurgulamaktadır. Sonuçların ayrıca yöneticiler için de önemli pratik çıkarımları tartışılmıştır.
İş sıkıntısından mı yoksa iş yoğunluğundan mı? İş yükünün ve iş sıkıntısının günlük iş çıktıları üzerindeki etkilerinin çok düzeyli bir araştırması
This paper is produced from the unpublished PhD thesis entitled “Multilevel Investigation of the Effects of Workload and Job Boredom on Work Outcomes” written by Ayla Avcı under the supervision of Mehmet Çetin.
Keywords: Job boredom; Workload; Job stress; Job satisfaction; PANA; Emotional labor; İş sıkıntısı; İş yükü; İş stresi; İş tatmini; PANA; Duygusal emek